Kedudukan Anak Luar Kawin dalam Sistem Waris Adat Sabu: Praktik Bui pa Studi atas kepue - Rayi Kharisma Rajib; Intan Salwa Puspita Hapsari; Dewi Latifah Azzahra Noor (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Children born out of wedlock often face limited rights under various legal systems, including both national and customary law. In the context of the Sabu indigenous community in East Sabu Subdistrict, Sabu Raijua Regency, there is a unique concept known as bui pa kepue, which literally means